Knowledge flow management supporting complex problem solving: learning spectrum and its infrastructure. (27th February 2007) - Dou, Wanchun; Liu, Xiping; Chen, Guihai; Cheung, S.C.; , Shijie Cai
Knowledge Management (KM) concerns innovating, spreading, sharing and using of knowledge assets. Dynamic knowledge flow management consists of cognition-compliant knowledge transferring and propagation for facilitating problem solving, which is a novel research issue in the KM domain. In this paper, the cognition is treated as the reflection-based knowledge application process related to problem solving and the cognition-compliant knowledge transferring and propagation is implemented through learning. Learning spectrum engaged in knowledge flow is explored from two aspects: depth learning and breadth learning corresponding to meta-cognition and group-cognition, respectively. Our work is based on a motivating example derived from New Product Development (NPD). To meet the globally distributed tendency of complex problem solving with cognitive intention, the infrastructure of Problem Solving Environment (PSE) based on Knowledge Grid (KG) scenarios is explored to facilitate web-based complex problem solving. At last, the conclusions are presented.